Análisis de la producción y comercialización de queso fresco en una hacienda del cantón Santa Rosa - Capelo Pontón, Patricio (2006)
The present investigation was carried out it in the farm “Los Cabuyos” which belongs to the Santa Rosa county; the objectives of the present work were: 1. To determine the production cost of a pound of cheese in the farm “Los Cabuyos”; 2. to evaluate the profitability of the cheesemaker production; 3. to analyze the commercialization of the cheese that was produced in the farm during the last year. During 30 days were obtained data of production as financial. The cost of pro-ducing one of a pound of cheese is $ 1,50, while the sale price is of $ 1,75; generating a profitability or net utility in the year of $ 4 188, 59; the sales are not carried out it taking the product from the facilities toward to warehouse, but rather the buyer arrives and it proceeds to place the cheese in bags with the own logo and it takes away them for the respective commercialization. The point of annual balance in prod-uct units is of 8 079 pounds while the monetary one is $ 20 198,42.